THE WOMEN’S MASCULINITY IN FANTASTIC BEASTS AND WHERE TO FIND THEM (2016) - Safanah, Qayla Putri; Sudarisman, Yoga (Saksama: Jurnal Sastra, 2023)
Film is a field of study that is very relevant to the analysis of human values, one of which is the value of masculinity. This study was conducted to determine the masculinity presented through language signs, verbal and non-verbal signs in the film Fantastic Beasts and where to Find Them (2016). The analysis technique used in this study is descriptive qualitative which refers to the female character character approach in the film Fantastic Beasts and Where to Find Them (2016) through the analysis of masculinity John Archer and Barbara Lloyd.Based on this level and the results of this study, researchers see that the film Fantastic Beasts and Where to Find Them (2016) provides an overview of the forms of masculinity, according to the concept of stereotype masculinity that is closely related and cannot be separated from the patriarchy culture and try to change the main stereotype In this film that women do not have to be at home and do not have the right to argue, but brave and firm in doing something or in making decisions. Women's masculinity is described not only about the style of dress or physically but through logical thinking and has a high leadership spirit.